Exercise algebra.equations.linear.balance

Description
Solve a linear equation using only balance rules.

Derivation

1-(4*x+2)/3 == 3*x-(5*x-1)/4
algebra.equations.linear.balance.remove-div, factor=12
12+4*(-4*x-2) == 36*x+3*(-5*x+1)
algebra.equations.linear.balance.distribute
12-16*x-8 == 36*x-15*x+3
algebra.equations.linear.balance.collect
4-16*x == 21*x+3
algebra.equations.linear.balance.var-right-plus, term=16*x
4 == 37*x+3
algebra.equations.linear.balance.con-left-minus, term=3
1 == 37*x
algebra.equations.linear.balance.scale-to-one, factor=37
1/37 == x
algebra.equations.linear.flip
x == 1/37